Corrosion studies on Fe‐30Mn‐1C alloy in chloride‐containing solutions with view to biomedical application. Issue 2 (16th August 2017) - Gebert, A.; Kochta, F.; Voß, A.; Oswald, S.; Fernandez‐Barcia, M.; Kühn, U.; Hufenbach, J.
Abstract : Austenitic Fe‐30Mn‐1C (FeMnC) is a prospective biodegradable implant material combining high mechanical integrity with adequate corrosion rates. The fast solidified TWIP alloy, its constituents and 316L stainless steel were electrochemically analysed in various electrolytes at 37 °C under laminar flow. Potentiodynamic polarization tests were conducted in Tris ‐buffered simulated body fluid (SBF), in Tris ‐buffered saline (TBS) and in 150–0.15 mM NaCl solutions (pH 7.6, 10, 5, 2) to study initial corrosion stages. Active dissolution of FeMnC is revealed in all electrolytes and is discussed on basis of the Fe and Mn behaviour plus is compared to that of 316L. The role of Tris ( Tris (hydroxymethyl)aminomethane) as organic buffer for SBFs is critically assessed, particularly with view to the sensitivity of Fe. SEM studies of FeMnC corroded in NaCl revealed preferential dissolution along Mn‐rich grain boundary regions. Static immersion tests of FeMnC in SBF with surface and solution analyses (SEM/EDX, XPS, ICP‐OES) indicated that dissolution processes interfere with the formation of permeable surface coatings comprising hydroxides and salts. Abstract : The Fe‐30Mn‐1C TWIP alloy is a prospective material for biodegradable implants with tailored microstructures yielding suitable properties. This work looks at the initial stages of the alloy degradation. Its actively dissolving nature is shown in different electrolytes from SBF to simple NaCl solutions and discussed based on Fe and Mn behaviour and relative to that of 316L SS.